PERANCANGAN SISTEM INFORMASI PEMESANAN KAMAR HOTEL BERBASIS ONLINE - Minda Mora Purba (JURNAL MITRA MANAJEMEN, 2020)
AbstractHotel room booking information system is one of the implementation of the Business to Customer which includes information on booking a room available, the cost of the bill upon check-out which includes room rental charges, restoration, laundry and other costs. With the application of information systems is expected to improve service and provide information about booking a room completely and quickly to guests, especially during holidays, when weekday or during the weekend, avoid going double booking and also can provide accurate information about the number of empty rooms and can provide information if there is a change of data or costs. Keywords: information systems, reservation, e - business,  internet